2018
DOI: 10.1007/s00405-018-4908-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional and cosmetic donor site morbidity of the radial forearm-free flap: comparison of two different coverage techniques

Abstract: The direct closure procedure is quick, simple and can be performed without secondary donor site morbidity. For wound healing, cosmetic and function of the forearm and hand, no inferior results can be measured for the direct procedure compared to the indirect coverage technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Wirthmann et al 12 reported that the satisfaction score for the esthetic appearance of the donor site after RFF flap surgery was 3.42 on average, which was acceptable, and the Vancouver Scar Scale resulted in a value of 4.2, representing a good result. Others have introduced different techniques of coverage of the donor site to improve the cosmetic results, including porcine collagen membrane, 13 acellular matrix, 14 autologous fat transplantation, 15 and local or distant full‐thickness skin graft 16 . All studies have reported satisfactory results, indicating that donor site appearance might not be of concern if appropriate modified methods were used.…”
Section: Discussionmentioning
confidence: 99%
“…Wirthmann et al 12 reported that the satisfaction score for the esthetic appearance of the donor site after RFF flap surgery was 3.42 on average, which was acceptable, and the Vancouver Scar Scale resulted in a value of 4.2, representing a good result. Others have introduced different techniques of coverage of the donor site to improve the cosmetic results, including porcine collagen membrane, 13 acellular matrix, 14 autologous fat transplantation, 15 and local or distant full‐thickness skin graft 16 . All studies have reported satisfactory results, indicating that donor site appearance might not be of concern if appropriate modified methods were used.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Pirlich et al compared functional outcomes between donor-site closure with an FTG or direct closure; however, no substantial difference in pain incidences was found between the two techniques. 28 Four studies used flaps for donor-site closure, including an anterolateral thigh flap 29 , an ulnar-based transposition flap 13 , a bilobed flap 30 , and a keystone flap 19 , however no considerable differences compared to skin graft closure were found. The difficulty in distinguishing the origin of donor-site pain between the different nerves or skin grafts emphasizes how little is known regarding this problem so far, and highlights the importance of investigating this in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The complications of this method are relatively common, and the aesthetic result is sometimes pure. Therefore, a number of alternative methods have been used: full thickness skin graft, local skin flap, tissue expansion, vacuum assisted closure (VAC), cell cultures, synthetic skin substitutes (35)(36)(37)(38)(39)(40)(41)(42)(43)(44). No one of these is ideal and many researches are still focused on the donor site of RFF (32,34).…”
Section: Discussionmentioning
confidence: 99%